Early Maladaptive Schemas Are Highly Indicative of Compulsive Sexual Behavior. Issue 2 (June 2021) - Efrati, Yaniv; Shukron, Ortal; Epstein, Robert
Unlike the consequences of compulsive sexual behavior (CSB) and the profile of people with CSB that were extensively studied, the cognitive distortions that might be responsible to the development and maintenance of CSB are less understood. In Study 1 ( n = 68), we examined intercorrelations between CSB and early maladaptive schemas among a sample with clinical CSB (Sexaholic Anonymous; SAs). In Study 2 (sex offenders; n = 103, and violence offenders; n = 81), we examined the intercorrelations between CSB and early maladaptive schemas among a sample with a sexual deviance but non-clinical levels of CSB. Results revealed that early maladaptive schemas are highly indicative of CSB severity. We discuss the implication of the study for the study and therapy of CSB.